Faktor-faktor Risiko Kualitas Tidur pada Pasien Kritis: Scoping Review: Faktor-faktor Risiko Kualitas Tidur pada Pasien Kritis: Scoping Review - Irni Fuzi Wijayanti; Desy Listyaningrum; Sri Setiyarini (Poltekkes Kemenkes Malang, 2025)
Background: Sleep is a psychological need that is often neglected in critically ill patients. Many factors contribute to poor sleep quality in critically ill patients. Current risk factors for sleep quality need updating. Objectives: To map the risk factors affecting sleep quality in critically ill patients. Methods: Scoping review was conducted on online databases, including ScienceDirect, Scopus, PubMed, and Google Scholar. There were 16 relevant studies published from 2018 to May 2023 that met the eligibility criteria. Article screening was carried out by two researchers, any differences of opinion were resolved by consensus. Outcomes: Sixteen studies identified premorbid, disease-related, and ICU-related factors (environmental, pharmacological, and respiratory & ventilation) as risk factors for sleep quality in critically ill patients. Noise, light exposure, nursing interventions are factors related to the ICU environment that are most commonly reported as disturbing. Conclusion: This review complements previous circulation systems to help nurses categorize patients who are at greatest risk for poor sleep quality according to PADIS guidelines, as well as assist nurses in developing multi-intervention programs that can improve sleep quality in critically ill patients. Keywords: Critically ill; sleep disorders; sleep quality